A new Early Cretaceous enantiornithine (Aves, Ornithothoraces) from northwestern China with elaborate tail ornamentation. Issue 1 (2nd January 2016) - O'Connor, Jingmai K.; Li, Da-Qing; Lamanna, Matthew C.; Wang, Min; Harris, Jerald D.; Atterholt, Jessie; You, Hai-Lu
ABSTRACT: We provide a detailed description of a well-preserved enantiornithine specimen (GSGM-05-CM-004) from the Lower Cretaceous (Aptian) Xiagou Formation of northwestern Gansu Province, China, for which we erect the new taxon Feitianius paradisi, gen. et sp. nov. This specimen has a distinctive pelvic morphology and can be further distinguished from all other Mesozoic birds by a unique caudal plumage formed by multiple rectricial morphotypes. This newly documented tail morphology reveals a previously unrecognized level of complexity in the plumage of basal birds. This complex tail-feather morphology has a parallel in extant sexually dimorphic birds in which the males have the most altered tails; thus, we identify this specimen as male. Ornamental tail morphologies, such as the novel tail plumage described here, dominate Enantiornithes. This reinforces hypotheses that sexual selection was a major driving force in the evolution of basal bird plumage. http://zoobank.org/urn:lsid:zoobank.org:pub:8BEF4422-58C5-487B-B76A-51C5855CF87B SUPPLEMENTAL DATA—Supplemental materials are available for this article for free at www.tandfonline.com/UJVP Citation for this article: O'Connor, J. K., D.-Q. Li, M. C. Lamanna, M. Wang, J. D. Harris, J. Atterholt, and H.-L. You. 2015. A new Early Cretaceous enantiornithine (Aves, Ornithothoraces) from northwestern China with elaborate tail ornamentation. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1054035.